What's ours is yours: recall of history for lesser-known countries is guided by one's own national history. Issue 4 (21st April 2019) - Cyr, Travis G.; Hirst, William
ABSTRACT: The present studies examine how people recall history. Sometimes, certain national histories are well known and sometimes they are not. We propose that, under certain circumstances, culturally distinctive representations of typical national histories can be used to guide recall, particularly in cases where the history is not well known. We focus on three national samples with varied levels of knowledge about each history: Great Britain, India, and the United States. In Study 1, we establish typical historical event templates for each nation consisting of events that a large proportion of participants from each sample identify as important in a typical nation's history. We examine points of divergence between the different groups' typical event templates and the valences of these events. In Study 2, we test and find that, in conditions of less knowledge, participants tend to refer to particular historical events that coincide with events unique to their own group's typical history. In Study 3, we demonstrate that this effect can be found even when a group possesses a reasonable amount of knowledge about the target country. We conclude by discussing the implications in relation to how such a retrieval strategy might inform interpretations of events in the present.